Formação inicial de professores do Ensino Fundamental I: da polivalência à interdisciplinaridade - Barros, Kelly Cristina da Silva (2016)
When the theme is teachers initial training to the Basic Educacion, the first element that emerges as a research focus is the role of polyvalence in the professional exercise.This perspective has the intention to ensure in its formation the comprehension of a global pedagogy that in one side meets the students needs and interests and in the other side encourages the teacher to realize the knowledges comprehensively and articulated, thus resulting a polyvalent teacher.There is a tension that characterizes this polyvalency: the teacher is seen as a professional that masters the knowledge of different curricular components and at the same time, acts in the student development under his responsibility.Therefore, the formation understands that this role must be to exercised by only a professional who meets these specificities. It regards a possible action since subsidized by criticizes view of the curriculum and an oriented learning to the inter and transdisciplinary. In this assignment, by a documentary research and bibliographic, has been identified that the polyvalency in the early years must be understood as a general skills able to form humam being in all dimensions; however, it is necessary not to treat as a mult task professional synonymous, in other words, that one fulfills many functions, without articulate them. This teacher must then adopt an interdisciplinary articulated action in many knowledge, as well as to understand the development and the learning of his student, from the social, cognitive and emotional point of view. In short, it regards a polyvalent teacher turning himself into an interdisciplinary professional